A retrospective study of quadrigeminal arachnoid cysts diagnosed by Magnetic Resonance Imaging and Computed Tomography in 26 dogs - Alves, Lidiane S. [UNESP]; Rodriguez, Diego [UNESP]; Machado, Vânia M.V. [UNESP]; Mamprim, Maria J. [UNESP]; Vulcano, Luiz C. [UNESP]; Amorim, Rogério M. [UNESP] (FapUNIFESP (SciELO), 2018)
Arachnoid cysts are accumulations of cerebrospinal fluid that occur within the arachnoid membrane due to the splitting or duplication of this structure. The aim of this retrospective study is to report the occurrence of this condition in 26 dogs, as well as to describe the findings of computed tomography imaging and magnetic resonance image scans and to correlate these with the clinical signs. A prevalence of the condition was observed in males, predominantly in the small breeds Miniature Pinscher and Shih Tzu, with age raging from 2 months to 9 years. The mainly clinical signs observed in these dogs were seizures and cerebellar ataxia. The study concluded that in 17 dogs the quadrigeminal arachnoid cyst was regarded as an incidental finding, in 6 dogs this condition was regarded as the determinant cause of the clinical signs, and in 3 dogs some clinical signs were associated with arachnoid cyst, but they also presented clinical signs involving others sites of intracranial lesion.
Keywords: Brain diseases; Cerebellar ataxia; Computed Tomography; Dogs; Hydrocephalus; Magnetic Resonance Imaging; Patology; Quadrigeminal arachnoid cysts; Seizures